Pengaruh Likuiditas, Solvabilitas, Ukuran Perusahaan, dan Ukuran KAP terhadap Audit Report Lag dengan Profitabilitas sebagai Variabel Intervening pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Fatahurrazak Fatahurrazak; Fatahuddin Fatahuddin; Fanny Hidayati Eka Putri; Ibnu Satria (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2024)
The purpose of this study was to analyze the effect of Liquidity, Solvency, KAP Size, and Company Size on Audit Report Lag with Profitability as a moderating variable in transportation and logistics sector companies listed on the Indonesian stock exchange for the 2019-2022 period. The samples used in this study were 52 transportation and logistics sector companies listed on the Indonesian stock exchange for the 2019-2022 period. The sampling technique used was nonprobability sampling, namely saturated sampling (census). The research method uses a quantitative approach with the analysis of Partial Least Square (PLS) analysis techniques with the SmartPLS Version 4.0 program. The results, state that Liquidity has a positive and significant effect on Audit Report Lag. Solvency has a positive and significant effect on Audit Report Lag. KAP size has a positive and significant effect on Audit Report Lag. Company size has a positive and significant effect on Audit Report Lag. Profitability has a positive and significant effect on Audit Report Lag. Liquidity has a positive and significant effect on Profitability. Solvency has a positive and significant effect on Profitability. KAP size has a positive and significant effect on Profitability. Company size has a positive and significant effect on Profitability. Profitability cannot moderate the relationship between Liquidity on Audit Report Lag, Profitability cannot moderate the relationship between Solvency on Audit Report Lag, Profitability cannot moderate the relationship between KAP Size on Audit Report Lag, and Profitability cannot moderate the relationship between Company Size on Audit Report Lag.